Wearable android : android wear & google Fit app development - Mishra, Sanjay (Hoboken, New Jersey : John Wiley and Sons, Inc., 2015)
Providing relevant history, background and core concepts, this book covers wearable computing and wearable application development particularly for Android Wear (smartwatches) and Google Fit (fitness sensors). --
9.6.3.SensorEventDispatcher interface -- References and Further Reading -- 10.Real-World Applications -- 10.1.Real-World Applications -- 10.2.Handheld Application Extension -- 10.3.Home Automation -- 10.3.1.Home Entertainment -- 10.3.2.Gaming -- 10.4.Wearables at the Workplace -- 10.5.Fitness, Health, and Medical -- 10.5.1.Predictive and Proactive Consumer Health -- 10.5.2.Wearables for Medical Professionals -- 10.5.3.Wearables and Remote Medical Diagnostics -- 10.6.Industrial Manufacturing -- 10.7.Civic, Government, and Democracy -- References and Further Reading.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Wearable computers; Mobile apps; Mobile apps; Wearable computers; COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Electronic books